“Global Law” as Legal Super-System in Formation - Vladimir M. Shumilov (Московский журнал международного права, 2015)
The article contains the original author’s conception of Global Law and Global Normative System which takes into account in complex the whole line of juridical phenomena under conditions of Globalization. The Global Law appears as indissoluble unity of international law and national law systems in which aroused law blocs named supranational law and transnational law - all of them it’s Global Law System. It includes also the mechanisms of law regulations, law-consciousness on every level, functioning law regimes and so on. Global Law System is hierarchical, structurally organized in definite mode, although it is under initial stage of forming. The States of west civilization type govern deliberately by the evolution of Global Law System in its interests exclusively, intending the supremacy of west (Anglo-Saxon) civilization in globalized World Order of XXI siecle. Global Law System is part of vaster Global Normative System.